Starvation before surgery: is our practice based on evidence? - Wilson, G; Dorrington, K (Oxford University Press, 2017)
The misery articulated by patients denied their morning ‘cuppa’ before coming to hospital for surgery is long-established and apparently ineradicable. A recent (February 2016) small audit of 44 adult patients admitted for elective surgery in five specialties in Oxford found that they had been denied (or denied themselves) drink for an average of 9 h (range 2–24 h) and food for 14 h (range 6–22 h) before being anaesthetized. These data are similar to those acquired 3 years earlier in the same trust in 190 elective patients in 17 surgical specialties, which showed that 70% of patients were fasted over twice the recommended length of time for both food (6 h) and drink (2 h), and 97% starved longer than required (Dr Medha Varanese, personal communication). This aspect of the preoperative care of patients in the immediate period before surgery does not bring us credit, even though its occurrence appears widespread and resistant to efforts aimed at change.